HALAL FOOD SUPPLY CHAIN (HFSC) AND SUSTAINABILITY CONCEPT - Musdiana Mohamad Salleh; Etty Harniza Harun (Journal of Islamic, Social, Economics and Development, 2022)
The halal food industry is currently one of the fastest-growing markets worldwide and has been identified as the new engine of economic growth. Despite the vast global Muslim population and the apparent demand for and consumption of halal food, the worldwide halal business produces food waste and jeopardizes environmental sustainability. Unfortunately, the importance of considering the environmental impact and sustainable business practices in managing halal supply chain management has not been discussed deeply by scholars and practitioners. To fill a gap in the literature and address existing practices, this paper seeks to discuss the sustainability concept concerning halal food supply chain management. This content analysis review is based on brief and limited insights from selected literature. This review will significantly aspire halal manufacturers in achieving the targets and indicators of the 2030 United Nations (UN) Sustainable Development Goals (SDG).